Relationship between shear strength and soil water characteristic curve of an unsaturated granitic residual soil - Kim Huat, Bujang; Ali, Faisal; Hashim, S. (Universiti Putra Malaysia Press, 2007)
The three shear strength parameters that are required to define a failure envelope of an unsaturated soil are c' (apparent cohesion),φ' (effective angle of friction), and φh (shear strength change with change in matric suction). A soil-water characteristic curve (SWCC) that relates the water content of a soil to matric suction is another important relationship in unsaturated soil mechanics. The SWCC essentially shows the ability of an unsaturated soil to retain water under various matric suctions. It has a similar role as the consolidation curve of a saturated soil that relates void ratio or water content to effective stress. The SWCC of a soil dictates the manner by which the permeability, shear strength and volume change of the soil will behave at different matric suctions upon drying and wetting. Since water can only flow through the water-filled pores, the SWCC therefore, essentially indicates the space available for the water to flow through the soil at various matric suctions. This paper describes a study on the shear strength-SWCC relationship that was carried out on an unsaturated granitic residual soil. It is observed that the failure envelope of an unsaturated soil is non-linear due to the non-linear soil water characteristic curve (SWCC). At low matric suctions, where the suction is lower than the air-entry value of the soil, the soil is at or near saturation condition and behave as though it is saturated. Consequently an increase in matric suction produces the same increase in shear strength as does an increase in net normal stress. However, at matric suctions higher than the air-entry value of the soil (> 200 kPa), the soil starts to desaturate. The increase in shear strength with respect to matric suction becomes less than the increase with respect to the net normal stress.